Physio-biochemical Response of Labeo rohita (Hamilton, 1822) fed with Antifungal Drug, Fluconazole - Saha, Himadri; Pal, Asim Kumar; Sahu, Narottam Prasad; Saha, Ratan Kumar; Goswami, Pritam (Fishery Technology, 2018)
An experiment was carried out to delineate thebiochemical responses in Labeo rohita fingerlings fedwith fluconazole (FLZ). There were twenty-fourtreatments divided into four groups (Control, T1,T2, and T3 fed with 0, 10, 20 and 30 mg FLZkg-1 body weight, respectively) and each group with6 exposure times (0, 6, 12, 24, 48, and 96 h) intriplicates. Biochemical parameters in plasma likeglutamate oxaloacetate transaminase (GOT),glutamate pyruvate transaminase (GPT), alkalinephosphatase (ALP), glucose, albumin, albuminglobulin ratio (A/G) were measured. Significantincrease (p